Laboratory measurements of ultrasonic velocities in CO2 saturated brines - Lebedev, Maxim; Bilenko, Olga; Mikhaltsevitch, Vassili; Pervukhina, M.; Gurevich, Boris (Elsevier, 2014)
The acoustic velocities in CO2-saturated brines were investigated and compared with velocities measured in pure brines in the range of temperatures (30 - 70 °C), pressures (2 - 38 MPa) and salinities (0 -100,000 ppm). It has been found that CO2 dissolution significantly changes the acoustic properties of brine. This change can be accounted for by a simple linear empirical equation.